Sustainable Development Strategy For Water Tourism Park Conservation Area In North Minahasa Regency - Mokoginta, Junio Marzuki Pratama; Paruntu, Carolus Paulus; Angmalisang, Ping Astony; Rompas, Rizald Max; Wullur, Stenly; Rondonuwu, Arie B. (Sam Ratulangi University, 2023)
Abstract The Government of Indonesia has targeted 32.5 million hectares of marine conservation areas or 10% of the total area of ​​Indonesian waters in 2030. The location of the Water Tourism Park Conservation Area of North Minahasa Regency has been reserved by the North Sulawesi Provincial Government through Governor Decree Number 407 of 2018 covering an area of ​​25,838.91 hectares. The purpose of this research is to formulate a strategy for the sustainable development of the Water Tourism Park Conservation Area in North Minahasa Regency. This research was conducted for 6 months starting from June - December 2022. The method used in this research is a descriptive research method with survey techniques, namely by collecting data through interviews with relevant stakeholders as respondents. The results of this study obtained 10 (ten) priority strategies for the sustainable development of Water Tourism Park Conservation Area in North Minahasa Regency which will be recommended to the local government, in this case the Marine and Fisheries Office of North Sulawesi Province and related stakeholders as suggestions and materials that can be proposed in the context of making public policy in the field of marine and fisheries. Key words: Conservation; North Minahasa; Sustainable Development; Strategy; Water Tourism Park Abstrak Pemerintah Indonesia telah menargetkan 32,5 juta hektar kawasan konservasi perairan atau 10% dari luas perairan Indonesia pada tahun 2030. Lokasi Kawasan Konservasi Taman Wisata Perairan Kabupaten Minahasa Utara telah dicadangkan oleh Pemerintah Provinsi Sulawesi Utara melalui Surat Keputusan Gubernur Nomor 407 Tahun 2018 seluas 25.838,91 hektar. Tujuan penelitian ini untuk merumuskan strategi pengembangan berkelanjutan Kawasan Konservasi Taman Wisata Perairan di Kabupaten Minahasa Utara. Penelitian ini dilakukan selama 6 bulan dimulai dari Juni - Desember 2022. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif dengan teknik survey, yaitu dengan cara pengumpulan data melalui wawancara dengan para stakeholders terkait sebagai responden. Hasil dari penelitian ini didapatkan 10 (sepuluh) strategi prioritas untuk pengembangan berkelanjutan Kawasan Konservasi Taman Wisata Perairan di Kabupaten Minahasa Utara yang akan direkomendasikan kepada pemerintah daerah dalam hal ini Dinas Kelautan dan Perikanan Daerah Provinsi Sulawesi Utara beserta stakeholders terkait sebagai saran dan bahan yang dapat dipertimbangkan dalam rangka pembuatan kebijakan publik pada bidang kelautan dan perikanan. Kata kunci: Konservasi; Minahasa Utara; Pengembangan Berkelanjutan; Strategi; Taman Wisata Perairan